Mathematical modelling and application of generalized unified power flow controller (GUPFC) steady state model for power system network. Issue 1 (2nd January 2020) - Sharma, Sandeep; Vadhera, Shelly
Abstract: Unified power flow controller (UPFC) is a unique kind of flexible alternating current transmission system device which can adjust power system parameters like active power, reactive power, and voltage magnitude as well as phase angle. Power transmission network is going to be more and more complex because of increase in multi-machine systems. In multi-machine systems, there is a need to adjust the power system parameters of two or more bus. In such cases, power system requirements are achieved by multiple UPFC. A reformed form of unified power flow controller which is defined as generalized UPFC comprises of one shunt converter and one then one series converter. Generalized UPFC is able to adjust the power system parameters for two or more bus or a subsystem. This paper provides the mathematical modeling of generalized UPFC in details. A novel approach based on a controlled current source employed for the scheming of phasor model of generalized UPFC in MATLAB. A comprehensive assessment is done between a phasor generalized UPFC model and multiple UPFC for congestion management of power system. The results establish the supremacy of generalized UPFC over multiple UPFC. This is the only work that brings forth for the first time, the time scheming of the phasor model of GUPFC in MATLAB/ Simulink.